Pengaruh penggunaan media papan perkalian terhadap hasil belajar matematika kelas II SDN Karangayar Gunung 02 Semarang - Reiza Putra, Aditya; Purnamasari, Veryliana; Riskiyati, Nur (COLLASE (Creative of Learning Students Elementary Education), 2025)
This research was taken based on the lack of students in facing challenges and feeling constrained in understanding the concept of multiplication, this was caused by the lack of application of concrete learning media in the mathematics learning process. The aim achieved in this research is to see the effect of using multiplication board media on student learning activities in mathematics learning multiplication material for class II SDN Karanganyar Gunung 02 Semarang. The method used in this research is a quantitative method with a research sample of 28 students. In collecting data, researchers used techniques in the form of test questions. The research results show that the pretest average is 66, while the posttest average is 91. The results of the hypothesis obtained through the Paired Simple T Test (t Test) show a significance value of 0.00 < 0.05. So in conclusion, there is an influence of the use of multiplication board media on class II multiplication learning outcomes at SDN Karanganyar Gunung 02 Semarang. Keywords : multiplication board, media, learning outcomes